2009
DOI: 10.1007/s00018-009-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid receptors protect from anoxic disruption of Na+ homeostasis via Na+ channel regulation

Abstract: Hypoxic/ischemic disruption of ionic homeostasis, especially Na + influx and K + leakage, is a critical trigger of neuronal injury/death in the brain. There is, however, no promising strategy against such pathophysiological changes to protect the brain from hypoxic/ischemic injury. Here we present an exciting finding that activation of delta-opioid receptor (DOR), which is highly expressed in the cortex, reduced anoxic Na + influx and K + leakage in the cortex by restricting Na + influx through voltage-gated N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 55 publications
5
51
0
Order By: Relevance
“…However, they differ widely with respect to their efficacies, potency, side-effects, clearance, and passage through the blood-brain barrier; refer to our previous articles [41, 53]. To the best of our knowledge, UFP-512 (H-Dmt-Tic-NH-CH[CH2-COOH]-Bid) is the most potent and specific DOR agonist, and Naltrindole is a well-accepted DOR antagonist [41, 53-58]. …”
Section: Opioid Receptors and Endogenous Opioidsmentioning
confidence: 99%
“…However, they differ widely with respect to their efficacies, potency, side-effects, clearance, and passage through the blood-brain barrier; refer to our previous articles [41, 53]. To the best of our knowledge, UFP-512 (H-Dmt-Tic-NH-CH[CH2-COOH]-Bid) is the most potent and specific DOR agonist, and Naltrindole is a well-accepted DOR antagonist [41, 53-58]. …”
Section: Opioid Receptors and Endogenous Opioidsmentioning
confidence: 99%
“…Opioid receptors are members of the G-protein-coupled receptor superfamily [76], and can functionally couple with ion channels, including Na + channels [16, 17, 77]. Our previous data implied an interaction between opioid receptors and Na + channels.…”
Section: Potential Mechanisms Of Acupuncture Inhibition Of Neuronamentioning
confidence: 99%
“…Activation of presynaptic DOR by enkephalin prevents the increase in neuronal Nav1.7 in the dorsal root ganglia, which relieves pain in diabetic neuropathy [17]. More recently, our studies indicated that DOR activation attenuates hypoxic K + -Na + homeostasis, which largely relies on DOR inhibition of Na + influx through Na + channels [16, 1822]. These results suggest that under pathological conditions DOR could mediate an inhibitory regulation of Na + channels in the brain.…”
Section: Potential Mechanisms Of Acupuncture Inhibition Of Neuronamentioning
confidence: 99%
See 1 more Smart Citation
“…10 VGSCs a subunits play an important role in different tissues. For example, Kang and coworkers 11 reported that VGSCs in the cortex were a major route for Na + influx during hypoxia and ischemia. Peripheral nerve injury caused by trauma or surgery may upregulate Nav1.3 and downregulate Nav1.8 in injured dorsal root ganglia, and intrathecal lidocaine pretreatment alleviates neuropathic pain by modulating Nav1.3 expression and decreasing spinal microglial activation.…”
Section: Introductionmentioning
confidence: 99%